2022
DOI: 10.54905/disssi/v26i125/ms318e2326
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of back pain among male teachers in Makkah region, Saudi Arabia: An analytic cross-sectional study

Abstract: Background: In primary care settings, back pain is the most prevalent complaint. Schoolteachers are at a higher risk of musculoskeletal issues.Several studies in Saudi Arabia have been looking into work-related musculoskeletal disorders, but the actual frequency and risks are unknown.Thus, this study's goal was to establish the incidence of back pain and its determinants among male schoolteachers in the Makkah, Saudi Arabia. Methodology:In this cross-sectional study, male schools in Makkah were divided into se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It was observed that most of the students were female (326; 65.9%), and the remaining were male (169; 34.1%). the majority of the students who responded to the questionnaire's their GPAs degree higher than 3 (i.e. BMI = 18.5-24.9), (82; 16.7%) were underweight (BMI = >18.5), (90; 18.3%) were overweight (BMI = 25.0-29.9), (30; 6.1%) were obese class-I (BMI= 30.0-34.9), (17; 3.5%) were obese class-II (BMI= 35.0-39.9) and only (8; 1.6%) were obese class-III (BMI= <40).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that most of the students were female (326; 65.9%), and the remaining were male (169; 34.1%). the majority of the students who responded to the questionnaire's their GPAs degree higher than 3 (i.e. BMI = 18.5-24.9), (82; 16.7%) were underweight (BMI = >18.5), (90; 18.3%) were overweight (BMI = 25.0-29.9), (30; 6.1%) were obese class-I (BMI= 30.0-34.9), (17; 3.5%) were obese class-II (BMI= 35.0-39.9) and only (8; 1.6%) were obese class-III (BMI= <40).…”
Section: Resultsmentioning
confidence: 99%
“…Musculoskeletal pain (MSP) is a common health problem, which affects many people, of different ages around the world. At some time in their lives, probably more than half of the general public will look for treatment for lower back pain (LBP) (Parreira et al, 2018;Alzahrani et al, 2022). According to a recent survey, 1.71 billion people worldwide suffer from musculoskeletal disorders (Cieza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Both extrinsic and intrinsic motivational factors influence instructors' choice of online PD over traditional face-to-face PD. According to Alzahrani (2021), factors such as personal interest, practical enhancement, and social contact motivated the participants' preference for online PD over the traditional face-to-face modality. Additionally, other factors, including independent learning, personalized learning, computer self-efficacy, social perception, external expectations, and improvement of skills, influenced instructors' motivation to choose online rather than face-to-face PD (Ibrahim & Nat, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among medical students at Jazan University revealed a very high prevalence of musculoskeletal pain (MSP) in the neck, shoulder, and lower back, of which lowback pain had the highest prevalence. The risk of MSP increased due to three main factors: history of trauma, depressive symptoms, and psychosomatic symptoms (Alzahrani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%